Self-assembled filomicelles prepared from polylactide-poly(ethylene glycol) diblock copolymers for sustained delivery of cycloprotoberberine derivatives - Xue Liu; Yanxiang Wang; Peng Yun; Xin Shen; Feng Su; Yangsheng Chen; Suming Li; Danqing Song (Elsevier, 2018)
Polylactide-poly(ethylene glycol) (PLA-PEG) block copolymers were synthesized by ring opening polymerization of l-lactide using a monomethoxy PEG (mPEG) as macroinitiator and zinc lactate as catalyst. The resulting diblock copolymers were characterized by 1H NMR and GPC. Polymeric micelles were prepared by self-assembly of copolymers in distilled water using co-solvent evaporation or membrane hydration methods. The resulting micelles are worm-like in shape as shown by TEM measurements. A hydrophobic anticancer drug, cycloprotoberberine derivative A35, was successfully loaded in PLA-PEG filomicelles with high encapsulation efficiency (above 88%). Berberine (BBR) was studied for comparison. In both methods, PLA-PEG filomicelles were prepared with a theoretical loading of 5%, 10% and 20%. Physical stability studies indicated that BBR/A35-loaded filomicelles were more stable when stored at 4 °C than at 25 °C. Compared with BBR-loaded filomicelles, A35-loaded filomicelles exhibited higher antitumor activity. Importantly, the in vitro cytotoxicity and stability of A35-loaded filomicelles evidenced the potential of drug-loaded filomicelles in the development of drug delivery systems.